أصول فقه الأقليات المسلمة وضوابطها بين النظرية والتطبيق : فتاوى المجلس الأوروبي للإفتاء والبحوث أنموذجا - مرزاقي، حليم (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study is an attempt to articulate the epistemplogical and methodological principles governing the jurisprudence pertaining to the Muslim communities living within non-Muslim societies, usually described as 'Muslim minorities', hence the identification of topic by the term 'jurisprudence of minorities'. The study has combined theory and practice, and made use of induction, analysis and critical comparison as methods of research in dealing with the different aspects of the subject. In order to attain this purpose, the researcher discussed and explicated the meaning of jurisprudence of minorities which is a new term and concept in Islamic jurisprudence both as legal theory and positive law. He also addressed a number of methodological issues concerning the exercise of legal inference (ijtihad) and issues of rulings (ifta') in dealing with the affairs of Muslim minorities. Then, the researcher focused on bringing into relief the major characteristics and features of Muslim minorities and the specific problems and challenges they face in their different environments. In so doing, the researcher relied on recent statistics and the prospects future of Muslim minorities as envisaged by social scientists. Finally, the researcher devoted a considerable part of the study to the practical aspect by undertaking an exposition, analysis and evaluation of juristic rulings (fatawa) issues by the European Council for Ifta' and Research which deal with different issues in the main areas of Islamic positive law, namely, rituals, financial transactions, family, social and political matters.The findings of this study included the jurisprudence of Muslim minorities which is the consideration of ease and license, provided they are subjected to the criteria and conditions governing them; the prevailing custom of the societies within which Muslim minorities live must be taken into account when inferring rules and issuing verdicts on juristic issues concerning Muslim minorities. Next, The body of fatawa and decisions issued by the European Council for Ifta' and Research is generally suitable to the conditions of Muslim minorities in European countries.